Person and family Law - Blanco-Morales Limones , Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The study of Chapter IV of the Preliminary Title of the Civil Code, regarding the persons and the family, of will focus on sections 1, 2, 3, 4, 6, 9, and 10 of Article 9, which are dedicated to personal status in its classic designation, with a brief reference to section 11, which addresses legal entities. The current wording of section 5, which refers to the Law on International Adoption, and section 7, which determines the applicable law for maintenance obligations among relatives in accordance with the Hague Protocol of November 23, 2007, on the applicable law for maintenance obligations or any legal text that may replace it, exempts us from their examination. These provisions reflect the labyrinth into which the solutions of Article 9 of the Civil Code have evolved, combining with others of differing origin, essence, and characteristics, sometimes discordant, in a state of normative overlap of unusual complexity.